2020
DOI: 10.21203/rs.3.rs-18054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of strontium ions with potential antibacterial activity on in vivo bone regeneration

Abstract: Background Bioactive glasses (BGs) have attracted added attention in the structure of the scaffolds for bone repair applications. Different metal ions could be doped in BGs to induce specific biological responses. Among these ions, strontium (Sr) is considered as an effective and safe doping element with promising effects on bone formation and regeneration. Methods In this experiment, we evaluated the antibacterial activities of the gelatin-BG (Gel-BG) and Gel-BG/Sr scaffolds in vitro. The osteogenic proper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In our study, the Mg discs displayed higher antibacterial activity than Mg‐Sc discs in S. aureus growth medium owing to their higher corrosion rate and pH values 6,13,38,61‐63 . To combat this reduction in antibacterial properties in Mg‐Sc, we added Sr to improve antibacterial properties of the alloy 64‐67 . Gao et al reported that the in vitro antibacterial tests on Mg‐Sr‐Ga alloy placed it on the top of the ranking list of germ‐killing ability.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In our study, the Mg discs displayed higher antibacterial activity than Mg‐Sc discs in S. aureus growth medium owing to their higher corrosion rate and pH values 6,13,38,61‐63 . To combat this reduction in antibacterial properties in Mg‐Sc, we added Sr to improve antibacterial properties of the alloy 64‐67 . Gao et al reported that the in vitro antibacterial tests on Mg‐Sr‐Ga alloy placed it on the top of the ranking list of germ‐killing ability.…”
Section: Discussionmentioning
confidence: 77%
“…Their results showed the antibacterial properties of pure Mg is improved through the addition of micro‐content of Ga and Sr (0.1 wt%) 68 . Additionally, Baheiraei et al showed Sr incorporation on Gelatin‐bioglass scaffolds effectively enhanced antibacterial activities against both S. aureus and Escherichia coli 64 . Moghanian and Araujo also confirmed the Sr substituted bioglass exhibited antibacterial effect against methicillin‐resistant Staphylococcus aureus bacteria 65,66 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although negative correlation of strontium may be explained by its cytotoxicity on bacteria [42,43], molecular biology studies have reported selective inhibition effects of magnesium and calcium on antibiotic-resistant bacteria. Magnesium and calcium may involve directly in the destabilization of the Staphylococcus aureus cell membrane [44].…”
Section: Args and Light Metalsmentioning
confidence: 99%